UJI STABILITAS FISIK SEDIAAN TEH SIRIH CINA (Peperomia pellucida) SECARA ORGANOLEPTIS BERDASARKAN METODE PENGERINGAN OVEN - Susi Andriani; Fadhilah Buamona (Jurnal Buana Farma, 2024)
Tea bags are favored by people, they are easy to make and practical. There are not many teas on the market that have the properties of lowering cholesterol and uric acid. The community has made a simple preparation of Chinese betel tea for generations. The content of Chinese betel leaves are flavonoid, alkaloids, tannins, and saponins. This study aims to determine the stability of tea with accelerated testing frequency, namely organoleptic test, pH test for 3 months and hedonistic test to 24 respondents with corn sugar and without corn sugar. Making tea using oven drying. The method with an observation instrument is to make simplisia. Drying shrinkage was 7.6%. Storage of tea is carried out at room temperature 30C and gives an overview for 12 weeks the condition of the tea is still stable, this is evidenced by organoleptic tests on color, smell, and taste as well as hedonistic tests by concluding respondents. Organoleptic test results show that tea with oven drying is relatively stable at 12 weeks without any changes in color, taste and smell where the distinctive smell of Chinese betel leaves is strong, the green color is slightly brownish and the taste is typical of Chinese betel leaves. The pH test on day 21 was 4.2, day 42 was 4.5, day 63 was 4.7 and day 84 was 4.8, The pH results below 5 indicate that the tea is still suitable for consumption. Hedonistic test on 24 people obtained 100% liked tea with corn sugar.